Pemanfaatan Pupuk Organik Cair (POC) Hepagro Bagi Pertumbuhan Green Cabomba (Cabomba caroliniana) Secara Aquascape - Liswandi, Liswandi; Ezward, Chairil; Wahyudi, Wahyudi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Aquascape is the art of arranging water plants, rocks, sand, coral and ornamental fish placed in an aquarium so that it gives the effect of gardening in water. Green Cabomba (Cabomba caroliniana) is an aquatic plant. Hepagro Liquid Organic Fertilizer (POC) is a liquid fertilizer resulting from the fermentation of micro-organisms made from industrial liquid waste based on the nutrient content of Hepagro POC Carbon (C), Phosphorus (P), Nitrogen (N), Potassium (K), Calcium (Ca) and Magnesium (Mg). This research aims to determine the effect of Hepagro liquid organic fertilizer (POC) on the growth of Green Cabomba (Cabomba caroloniana) plants. The research design used was a Non Factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, consisting of P0 (No Hepagro Fertilizer), P1 (12.5 ml/l Hepagro Fertilizer), P2 (25 ml/l Hepagro Fertilizer ) and P3 (Hepagro Fertilizer 37.5 ml/l). Based on the research results, giving Hepgro POC treatment had a real influence on all observation parameters with the best treatment being P3 37.5 ml/l with plant height 22.17 cm, stem diameter 2.21 mm, root length 7.10 cm and plant fresh weight 3 .95 grams.